Effect of Impossible Trinity on Investment in Developing Countries: Evidence from Africa - Yves Claude Nshimiyimana; Theogene Habimana (Research Parks Publishers, 2022)
We are concerned about which choice among the trilemma index affects investment in developing countries. We use the empirical method to study Africa's trilemma index and investment. Using Ordinary Least Squares and Two Stages Least Squares estimators with a dataset covering 39 African countries over an extended period of 30 years, we indicate the effect of the trilemma index on investment in Africa is still a big challenge to control. The main reason is that most African countries do not have well-developed monetary policy and autonomy and rely on foreign direct investment (FDI). On the other hand, they do not have enough capacity to control exchange rate stability. The endogeneity tests support our findings.